Pengaruh Leverage, Likuiditas, dan Kepemilikan Manajerial terhadap Ketepatan Waktu Pelaporan Keuangan - Diana Agustin; N. Heriyah; Azwani Aulia (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2023)
This research focuses on the factors that can influence the timeliness of financial reporting. The data used to support this research are secondary data published on the Indonesia Stock Exchange and the official websites of the companies. The research method used is a quantitative research method with a descriptive approach. Descriptive statistical analysis, classical assumption tests, multiple linear regression, correlation coefficients, determination coefficients, and hypothesis testing are used to analyze the issues in this research. The partial results of the study indicate that leverage and liquidity have an influence on the timeliness of financial reporting, while managerial ownership does not have an influence on the timeliness of financial reporting. Meanwhile, the simultaneous results of the study indicate that leverage, liquidity, and managerial ownership collectively have an influence on the timeliness of financial reporting.